2012
DOI: 10.1039/c2fd20031g
|View full text |Cite
|
Sign up to set email alerts
|

Stability of aqueous food grade fibrillar systems against pH change

Abstract: We report that the stability of an aqueous food grade fibril system upon pH change is affected by the presence of peptides that are formed during the process of fibril formation. We discuss several other relationships between food relevant properties and nano-scale characteristics, and compare these relationships for aqueous fibril systems to those of oil based fibril systems. In such fibril systems, dynamics, self-organisation, and sensitivity to external conditions, play an important role. These aspects are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 63 publications
7
43
0
Order By: Relevance
“…In contrast to these findings fibrils maintain their structure at pH's up to 8.0 when pH is increased after fibrillation. However, in a critical pH region (5-6), the fibrils aggregate and collapse (Jung and Mezzenga, 2009;Kroes-Nijboer et al, 2012a).…”
Section: Fibril Formation At Different Ph Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these findings fibrils maintain their structure at pH's up to 8.0 when pH is increased after fibrillation. However, in a critical pH region (5-6), the fibrils aggregate and collapse (Jung and Mezzenga, 2009;Kroes-Nijboer et al, 2012a).…”
Section: Fibril Formation At Different Ph Valuesmentioning
confidence: 99%
“…The authors identified the fraction of non-aggregated peptides in fibril solutions as being mainly responsible for the turbidity observed when pH is increased to pH 5.0 which is the isoelectric point of b-lactoglobulin. The potential of fibrils to solidify oil phases as alternative to triglycerides and plant sterols in food was also discussed by the same authors (Kroes-Nijboer et al, 2012a Fibrils were shown to exert a highly elastic behaviour at o/winterfaces during interfacial shear rheology analyses . Quite recently, Rühs et al (2013) showed distinct differences in shear and dilatational rheology properties of the different fractions present in fibrillar solutions, i.e.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The acidic hydrolysis of proteins including ␤-lactoglobulin during the fibrillation process [15] is also noteworthy when assessing gelation. We argue that since not all of the acid-generated peptides are converted to fibrillar structures [14] and so remain as individual entities within the fibrillation-underwent solution, can impact the gelation behavior and gel characteristics of fibril solution. Non-fibrillated peptides possess much more negatively-charged carboxyl groups than parent protein molecules at identical mass concentrations, thus could be cross-linked ionically in a more efficient way than protein counterparts.…”
Section: Fabrication Of Cold-set Hydrogels From Heat-denatured or Fibmentioning
confidence: 99%
“…Veerman et al [2] also obtained calcium-induced cold-set hydrogels from fibrillated ␤-lactoglobulin solution at a lower protein concentration in comparison with heat-denatured solution. Fibrillar structures can form a space filling network at low volume fractions because of significant contour length, high aspect ratio and their random orientation [14]. The acidic hydrolysis of proteins including ␤-lactoglobulin during the fibrillation process [15] is also noteworthy when assessing gelation.…”
Section: Fabrication Of Cold-set Hydrogels From Heat-denatured or Fibmentioning
confidence: 99%